Political Theology, Democracy, and the Exception in the Egyptian Revolution. Issue 7 (3rd October 2017) - Scherer, Matthew
Abstract : As the sixth anniversary of the 2011 protests in Tahrir Square passes, those uprisings and the events that followed continue pose important challenges not only for students of Middle Eastern and North African politics, but also for students of political theory and political theology. While scholars debate the extent to which the "Arab Spring" has amounted to a truly revolutionary turn of events, it is commonly accepted that the protests that swept the region were exceptional in their unanticipated and profound disruption of ordinary affairs. Under the influence of Carl Schmitt's theory of sovereignty, "the exception" has become a key figure in contemporary reflections on political theology, but attention to events in Egypt suggests that the familiar figure of the exception has not yet been mined for all of its implications for democratic practice. Slipping below grand articulations of the exception as a moment of sovereign decision, or as the suspension of the law, this essay turns its attention to the minor, everyday, background patterns of exceptionality that accompany the emergence of democratic practices outside the purview of the sovereign state. I argue that there is an intimate connection between the forms of exceptionality produced by longstanding practices of Egyptian secularism, the forms of exceptionality peculiar to the 2011 uprisings and their aftermath, and the forms of exceptionality that both make and unmake democratic practices. My argument has three parts: first Egyptian secularism is a process that manages and transforms authorized forms of Islamic practice, while at the same time producing exceptional formations, of which the Muslim Brotherhood is a key example; second that revolutionary politics can be understood as a matter of opening and sustaining the kind of exceptional circumstances that attended the 2011 uprisings, and that this can be usefully framed as an open-ended process of conversion; third that democratic practice requires courting both kinds of exception, despite their challenges, ambivalences, and potential dangers.